Exploring student satisfaction and future employment intentions: A case study examination: is there a link between satisfaction and getting a job?. Issue 2 (10th April 2018) - James, Melissa; Yun, Dongkoo
Abstract : Purpose: The purpose of this paper is to explore the factors that affect higher education student satisfaction and to understand students' perceptions of their academic success and future employment expectations at a particular institution. Design/methodology/approach: This study analyzes institutional performance related to students' satisfaction and their preparedness for future employment endeavours. The questionnaire is designed specifically for students who are eligible to graduate, and the survey is implemented over the institutional website via the student portal and a total of 750°-seeking undergraduate students (target population) are invited to participate. Findings: The descriptive results of this study suggest that while student satisfaction may be relatively similar for all academic programmes, there are differences in the perception of career expectations based on chosen academic programme. Most notably, the results also indicate students' expectations for employment did not have a negative effect on their satisfaction with the higher education institution (HEI). In contrast, they were mostly satisfied with their academic and personal development. In essence, they felt prepared for the workplace and satisfied with the skills and knowledge developed at a university, regardless of job expectations. This paper suggests that institutions may wish to heighten their focus on academic factors in their efforts to retain students and improve their student academic experience. Originality/value: This study is conducted at a small-sized (less than 5, 000 students) higher institution in Canada that primarily provides undergraduate courses and focusses on students' employment expectations and their rating of the academic experiences. This study can assist HEIs in developing policies related to student retention and success. HEIs may find this study useful in developing policies and programmes related to transitioning from undergraduate studies to the workplace.